(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article focuses on the deportation of certain ethnic groups within the USSR during the challenging circumstances of the Great Patriotic War. Special attention is given to comparing the experiences of deported populations with those who remained in territories occupied by the invaders. The article concludes that the deportation and administrative coercion of some ethnic groups in the USSR between 1941 and 1954 were driven by the need to strengthen national security. It also highlights that the war brought immense sacrifices and that the entire population of the USSR endured unimaginable suffering and losses.